Parallel Dictionary Reconstruction and Fusion for Spectral Recovery in Computational Imaging Spectrometers - Hongzhen Song; Qifeng Hou; Kaipeng Sun; Guixiang Zhang; Tuoqi Xu; Benjin Sun; Liu Zhang (Sensors)
Computational imaging spectrometers using broad-bandpass filter arrays with distinct transmission functions are promising implementations of miniaturization. The number of filters is limited by the practical factors. Compressed sensing is used to model the system as linear underdetermined equations for hyperspectral imaging. This paper proposes the following method: parallel dictionary reconstruction and fusion for spectral recovery in computational imaging spectrometers. Orthogonal systems are the dictionary candidates for reconstruction. According to observation of ground objects, the dictionaries are selected from the candidates using the criterion of incoherence. Parallel computations are performed with the selected dictionaries, and spectral recovery is achieved by fusion of the computational results. The method is verified by simulating visible-NIR spectral recovery of typical ground objects. The proposed method has a mean square recovery error of ≤1.73 × 10−4 and recovery accuracy of ≥0.98 and is both more universal and more stable than those of traditional sparse representation methods.